Surgery for pelvic organ prolapse. Issue 4 (July 2016) - Patel, Devin N.; Anger, Jennifer T.
Abstract : Purpose of review: Surgical repair of pelvic organ prolapse remains one of the most commonly performed inpatient procedures. New evidence has helped establish risk factors for recurrence and helped define the outcomes of native tissue repairs. The role of transvaginal mesh and minimally invasive techniques continues to evolve. Recent findings: Recent emphasis on mesh complications and litigation has led to new research showing native tissue vaginal repairs to have higher success rates than previously reported. Mesh placement transvaginally also has acceptably low complication rates when performed with proper technique. Mesh augmentation for prolapse has low complication rates when placed abdominally. Minimally invasive techniques have reduced the morbidity of these abdominal procedures. Summary: Native tissue vaginal repairs have high success rates, as long as prolapse of the vaginal apex is identified and addressed when present. The number of procedures performed with mesh augmentation has declined, and surgeons who continue to perform them will likely be high volume technicians with good outcomes.